2016
DOI: 10.1136/bmjopen-2015-008988
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in university hospitals in Saudi Arabia: a systematic review

Abstract: ObjectivesTo identify the key issues, problems, barriers and challenges particularly in relation to the quality of care in university hospitals in the Kingdom of Saudi Arabia (KSA), and to provide recommendations for improvement.MethodsA systematic search was carried out using five electronic databases, for articles published between January 2004 and January 2015. We included studies conducted in university hospitals in KSA that focused on the quality of healthcare. Three independent reviewers verified that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…Nurses from different countries are likely to have different views on QNC because of differences in cultural backgrounds and perceptions of the characteristics of care. This finding is worth noting because many shortcomings, such as medical errors, poor performance, lack of positive organisational climate, insufficient resources and understaffing, have been reported in hospitals in Saudi Arabia (Alenezi et al, 2019;Aljuaid, Mannan, Chaudhry, Rawaf, & Majeed, 2016). These issues challenge nurses to improve their QNC as required in the clinical setting.…”
Section: Discussionmentioning
confidence: 94%
“…Nurses from different countries are likely to have different views on QNC because of differences in cultural backgrounds and perceptions of the characteristics of care. This finding is worth noting because many shortcomings, such as medical errors, poor performance, lack of positive organisational climate, insufficient resources and understaffing, have been reported in hospitals in Saudi Arabia (Alenezi et al, 2019;Aljuaid, Mannan, Chaudhry, Rawaf, & Majeed, 2016). These issues challenge nurses to improve their QNC as required in the clinical setting.…”
Section: Discussionmentioning
confidence: 94%
“…In a medical context, such communication barriers lead to poor service delivery. This outcome can be related to the studies conducted in other parts of the globe on the importance of language in facilitating communication between patients and healthcare givers (Al Hamid et al, 2017;Albougami, 2015;Almutairi, 2015;Aljuaid et al, 2016). For instance, Al Hamid et al (2017) revealed that communication barrier contributes to medicine-related problems among patients with cardiovascular diseases and diabetes since the healthcare giver finds it challenging to communicate with the patient about compliance and other vital issues.…”
Section: Discussionmentioning
confidence: 88%
“…Other previous studies also show that a language difference is a barrier to the provision of quality healthcare in Saudi Arabia (Albougami, 2015;Almutairi, 2015;Aljuaid, Mannan, Chaudhry, Rawaf, & Majeed, 2016). As Wong et al (2011) note, effective communication is an important component in a healthcare setting.…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Although limited research investigated the awareness and influence of the patientcentred approach among healthcare professionals and patients in the KSA, a systematic review investigated the quality of health care in university hospitals reported that the main factors that negatively influence delivering patient-centred 15 services were lack of communication with patients in terms of providing them with enough information and communicating in the Arabic language (Aljuaid et al 2016). …”
Section: Structure Of the Healthcare System And Current Physiotherapymentioning
confidence: 99%